2006
DOI: 10.1080/01490450600760658
|View full text |Cite
|
Sign up to set email alerts
|

Rock Biofertilizers withAcidithiobacilluson Sugarcane Yield and Nutrient Uptake in a Brazilian Soil

Abstract: The experiment was conducted with the aim to evaluate the effects of biofertilizers with phosphate and potash rocks and soluble fertilizers (Triple super phosphate and potassium chloride) in chemical attributes of a Brazilian tableland soil grown with sugarcane. The experiment was arranged in a completely randomized factorial design 2 × 4 × 3 + 1, with four replicates. Two varieties of sugarcane, three sources of P and K mixture (natural apatite + natural biotite; P + K biofertilizers with Acidithiobacillus an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
32
0
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 4 publications
9
32
0
6
Order By: Relevance
“…While leaf P and K contents increased with application rate for both soluble and biofertilizers, the increase was much stronger for soluble fertilizer, with the reverse pattern for Mg leaf content, similarly to berry nutrient concentrations. These results are similar to those found for sugarcane and melon (Stamford et al, 2006(Stamford et al, , 2008. Faria et al, (2004) .…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…While leaf P and K contents increased with application rate for both soluble and biofertilizers, the increase was much stronger for soluble fertilizer, with the reverse pattern for Mg leaf content, similarly to berry nutrient concentrations. These results are similar to those found for sugarcane and melon (Stamford et al, 2006(Stamford et al, , 2008. Faria et al, (2004) .…”
Section: Resultssupporting
confidence: 90%
“…Rock biofertilizers from P and K rocks plus sulphur inoculated with Acidithiobacillus have been applied with excellent results in different crops and soils of the rain forest zone and in the semiarid region of the Brazilian Northeast, as reported by Stamford et al, (2006Stamford et al, ( , 2007Stamford et al, ( , 2009), but no literature was found on biofertilizer usage on grapes, or on long-term field cultures.…”
Section: Introductionmentioning
confidence: 93%
“…However, the available K measured in the soil was highest after treatment with FNPK fertilizers, NPKB (ChCru 6 mg mL -1 ) and (ChFu 2 mg mL -1 ), with the addition of C. elegans. The effects of chitosan were likely observed in the treatments with higher amounts of substrates that were sulfur inoculated with Acidithiobacillus, as the acid production increases the available P and K in soil (Stamford et al, 2006(Stamford et al, , 2008. Furthermore, chitosan increased the levels of N, P and K in the substrate (Kowalski et al, 2006, Goy et al, 2009.…”
Section: Soil Attributesmentioning
confidence: 99%
“…Furthermore, chitosan increased the levels of N, P and K in the substrate (Kowalski et al, 2006, Goy et al, 2009. The application of sulfur with Acidithiobacillus must be thoroughly evaluated due to the acidification effect of sulfuric acid, which in some cases and particularly in acidic soils, may result in the displacement of exchangeable Al +3 that is harmful to plant growth (Stamford et al, 2006). The results of this study suggest that further investigation is necessary to evaluate the effect of amendments in different soils due to their effect on soil pH.…”
Section: Soil Attributesmentioning
confidence: 99%
“…An alternative for effective and economic fertilization is the use of biofertilizers made from phosphate and potash rocks with elemental sulfur inoculated with Acidithiobacillus. This combination achieves greater nutrient availability since the bacteria produce sulfuric acid, and thus increase both phosphorus and potassium availabilities, with results comparable to traditional fertilizers in several experiments with different economic crops (Stamford et al, 2006;van Straaten, 2007;Stamford et al, 2008).…”
Section: Introductionmentioning
confidence: 91%